Draft 7th Five Year Plan 1985-90 and Annual Plan 1985-86 Vol. X Jammu and Kashmir Government - Planning Commission (Planning Commission, 1985)
An outlay of Rs. 250.00 lacs was approved for the 6th five year plan against which an amount of Rs. 226.56 lacs is to be spent by the end of the 6th Plan. Under this Sector an amount of Rs 64.64 lacs form as salaries and other revenue expenditure under different schemes of welfare, The same amount is proposed to be transferred to non-plan sector during 7th five year plan- Under this sector, schemes like Child Welfare/ Women Welfare/We fare of Handicapped/other Welfare schemes and implemented.
Planning and Development Department, Jammu and Kashmir Government